Drop profile analysis tensiometry under highly dynamic conditions - Karbaschi, M.; Bastani, D.; Javadi, A.; Kovalchuk, V.I.; Kovalchuk, N.M.; Makievski, A.V.; Bonaccurso, E.; Miller, R. (Colloids and surfaces. A, Physicochemical and engineering aspects, 2012)
The results of measured surface tension by the use of drop profile analysis tensiometry (PAT) under dynamic conditions indicate acceptable values at low Reynolds numbers, however for high Reynolds numbers show surface tension values significantly lower than the physical expected values. [Display omitted] ► Profile analysis tensiometry under dynamic conditions can be discriminated to three regions. ► Low Re number: deviations from Laplacian shape are small and the surface tension values are correct. ► Intermediate Re number: deviations from Laplacian shape are small but the surface tension values are significantly low. ► High Reynolds numbers: neither Std nor the obtained surface tension values are acceptable. Profile analysis tensiometry (PAT) is presently the most frequently used technique for measuring surface tensions of liquids. The basis of this methodology is however an equilibrium force balance as given by the Gauss–Laplace equation. Therefore, its application under dynamic conditions, i.e. for growing drops or bubbles, is questionable. We discuss the limits of the applicability of PAT under dynamic conditions by using a growing drop configuration equipped with a high speed video camera. The systems studied are the water/air and water/hexane interface. The obtained “dynamic” drop profiles are analyzed by fitting the classical Gauss–Laplace equation. The results are additionally compared with experimental data obtained from capillary pressure tensiometry. The analysis allows defining three different regions related to respective drop expansion rates.